Myocardial work indices in the short‐term prognosis of light‐chain cardiac amyloidosis: Incremental value beyond traditional staging models and echocardiographic parameters - Meng, Fangmin; Li, Jing; Zhao, Rui; Wu, Yuanfeng; Liu, Yu; Yang, Yiming; Yang, Yang; Zhou, Nianwei; Dong, Lili; Kong, Dehong; Chen, Haiyan; Shu, Xianhong; et al. (British journal of haematology, 2025)
Summary Light‐chain cardiac amyloidosis (AL‐CA) causes structural and functional cardiac impairment. Myocardial work (MW), integrating left ventricular strain with afterload, may improve risk stratification. This study assesses the prognostic value of MW in AL‐CA patients and its potential to enhance traditional staging models. We prospectively enrolled biopsy‐confirmed AL‐CA patients between 2022 and 2024. MW indices, including global work index (GWI) and global constructive work (GCW), were derived using EchoPAC 206. The primary outcome was all‐cause mortality. Among 96 AL‐CA patients (mean age: 62.8 ± 10.2 years; 70% male), 28 died during a median follow‐up of 190 days. Multivariate Cox analysis identified GWI and GCW as independent predictors of mortality after adjusting for creatinine, heart rate, New York Heart Association class, Mayo 2012 class and pleural effusion. Kaplan–Meier analysis showed worse survival for GWI ≤840 mmHg% or GCW ≤1031 mmHg%. The likelihood ratio χ2 test demonstrated that GWI and GCW significantly improved the predictive power of the Mayo 2012 and Euro 2015 models (p < 0.001). MW indices, particularly GWI and GCW, are independent predictors of short‐term mortality in AL‐CA patients, thereby improving existing risk models and providing valuable prognostic insights. Myocardial work parameters (global work index/global constructive work) improve risk stratification in light‐chain cardiac amyloidosis.